Unveiling the Bio-Inspired and Green Chemistry Potential of Ceylon and Cape Gooseberries through Comprehensive Nutritional Profiling - Razafimahefa Mirana Verohanitra; Razafindrazanakolona, Daniel; Ralaivaon-Tsitonta Jumael Edith Fabrice; Robijaona Rahelivololoniaina Baholy (Britain International of Exact Sciences (BIoEx) Journal, 2025)
This study meticulously investigates the chemical and nutritional profiles of two underexplored tropical fruit species indigenous to Madagascar: the Ceylon Gooseberry (Dovyalis hebecarpa) and the Cape Gooseberry (Physalis peruviana). Characterizing such native species is vital for diversifying food sources and enhancing nutritional security, particularly in biodiversity-rich regions.Systematic analyses performed across various plant compartments, notably their foliage, revealed a significant richness in essential micronutrients. Leaves of both species demonstrated substantial concentrations of potassium, phosphorus, iron, magnesium, and aluminum. Furthermore, Physalis peruviana leaves exhibited a particularly significant protein content, elevating their prospective utility beyond fruit consumption. This robust nutritional profile reinforces their potential as valuable, locally sourced ingredients to foster balanced diets in the region. Parallel to the nutritional assessment, empirical processing trials were initiated to ascertain the technological feasibility and quality attributes of derived products, focusing on wine. The fermentation processes consistently yielded wines categorized as dessert wines, which demonstrated stable physicochemical characteristics and promising shelf-life properties. This intrinsic stability, coupled with their unique profiles, suggests compelling added value within agro-food valorization strategies. Collectively, these findings underscore the considerable potential of both Dovyalis hebecarpa and Physalis peruviana for the innovative development of novel food products. Such initiatives not only contribute to agricultural diversification but also align seamlessly with circular economy principles by utilizing underexploited plant parts, and sustainable development by fostering local biodiversity and resource efficiency. This research provides a scientific basis for promoting the cultivation and processing of these indigenous fruits, contributing to economic growth and environmental stewardship.